A Lanthanum‐Filled Carbon–Boron Clathrate. (9th December 2020) - Strobel, Timothy A.; Zhu, Li; Guńka, Piotr A.; Borstad, Gustav M.; Guerette, Michael
Abstract: We report a carbon‐boron clathrate with composition 2 La@B6 C6 (LaB3 C3 ). Like recently reported SrB3 C3, [1] single‐crystal X‐ray diffraction and computational modelling indicate that the isostructural La member crystallizes in the cubic bipartite sodalite structure (Type‐VII clathrate) with La atoms encapsulated within truncated octahedral cages composed of alternating carbon and boron atoms. The covalent nature of the B−C bonding results in a hard, incompressible framework, and owing to the balanced electron count, La 3+ [B3 C3 ] 3− exhibits markedly improved pressure stability and is a semiconductor with an indirect band gap predicted near 1.3 eV. A variety of different guest atoms may potentially be substituted within Type‐VII clathrate cages, presenting opportunities for a large family of boron‐stabilized, carbon‐based clathrates with ranging physical properties. Abstract : High‐pressure synthesis reveals LaB3 C3, a La‐stuffed, carbon–boron clathrate in the bipartite sodalite structure. Trivalent La 3+ allows charge balance with the [B3 C3 ] 3− framework, resulting in a semiconducting material at improved synthetic conditions. Robust sp 3 covalent bonds produce high strength and hardness, while different guest atoms within the clathrate cages allow the possibility for tunable electronic properties.